The complexities of CACNA1A in clinical neurogenetics - Hommersom, Marina P.; van Prooije, Teije H.; Pennings, Maartje; Schouten, Meyke I.; van Bokhoven, Hans; Kamsteeg, Erik-Jan; van de Warrenburg, Bart P. C. (Journal of neurology, 2022)
Variants in CACNA1A are classically related to episodic ataxia type 2, familial hemiplegic migraine type 1, and spinocerebellar ataxia type 6. Over the years, CACNA1A has been associated with a broader spectrum of phenotypes. Targeted analysis and unbiased sequencing of CACNA1A result not only in clear molecular diagnoses, but also in large numbers of variants of uncertain significance (VUS), or likely pathogenic variants with a phenotype that does not directly match the CACNA1A spectrum. Over the last years, targeted and clinical exome sequencing in our center has identified 41 CACNA1A variants. Ultimately, variants were considered pathogenic or likely pathogenic in 23 cases, with most phenotypes ranging from episodic or progressive ataxia to more complex ataxia syndromes, as well as intellectual disability and epilepsy. In two cases, the causality of the variant was discarded based on non-segregation or an alternative diagnosis. In the remaining 16 cases, the variant was classified as uncertain, due to lack of opportunities for segregation analysis or uncertain association with a non-classic phenotype. Phenotypic variability and the large number of VUS make CACNA1A a challenging gene for neurogenetic diagnostics. Accessible functional read-outs are clearly needed, especially in cases with a non-classic phenotype.